Legal Protection of Double Certified Land Right Holders - Diaz Praba Wisudawanta (Universitas Islam Lamongan, 2025)
This research examines legal protection for holders of land rights with dual certificates in Indonesia. 1This paper discusses specific court cases. This research outlines the legal framework for land registration in Indonesia, emphasizing the government's responsibility to ensure legal certainty through land registration. 16 This also highlights the negative system in land registration, where a certificate is considered valid until proven otherwise in court. The main findings of this research aim to provide insight into the challenges of resolving land disputes and the need for effective legal protection for land rights holders in Indonesia.